Epidemiological Study on Metal Pollution of Ningbo in China - Zhou Li (International Journal of Environmental Research and Public Health, 2018)
Background: In order to search for effective control and prevention measures, the status of metal pollution in Ningbo, China was investigated. Methods: Nine of the most common contaminating metals including lead (Pb), cadmium (Cd), copper (Cu), iron (Fe), manganese (Mn), chromium (Cr), nickel (Ni), zinc (Zn), and mercury (Hg) in samples of vegetables, rice, soil, irrigation water, and human hair were detected using inductively coupled plasma-mass spectrometry (ICP-MS). Three different districts including industrial, suburban and rural areas in Ningbo were studied through a stratified random sample method. Results: (1) Among all of the detected vegetable samples, Cd exceeded the standard limit rates in industrial, suburban and rural areas as high as 43.9%, 27.5% and 5.0%, respectively; indicating the severity of Cd pollution in Ningbo. (2) The pollution index (PI) of Cd and Zn in soil (1.069, 1.584, respectively) suggests that soil is slightly polluted by Cd and Zn. Among all samples, metal contamination levels in soil were all relatively high. (3) A positive correlation was found between the concentrations of Pb, Cd and Cu in vegetables and soil; Pb, Cu, Cr and Ni in vegetables and irrigation water, as well as, Cu and Ni in rice and irrigation water; and, (4) Higher Pb and Cd concentrations were found in student scalp hair in both industrial and suburban areas compared to rural areas. (5) Hg and Pb that are found in human scalp hair may be more easily absorbed from food than any of the other metals. Conclusions: In general, certain harmful metal pollutions were detected in both industrial and suburban areas of Ningbo in China.